PRAKTIK PENGGUNAAN APLIKASI WHATSAPP SEBAGAI MEDIA KOMUNIKASI ORANG TUA DAN ANAK (STUDI ANAK YANG SEKOLAH DI LUAR KOTA/LUAR NEGERI) - Khaira Fitmi (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2024)
In the era of increasingly rapid development of the digital world, the use of communication media applications such as WhatsApp has become an inseparable part of communication, especially communication for parents and children who have distance-related problems. This journal aims to find out why they chose the WhatsApp application and how they practice using the WhatsApp application as a communication medium between parents and children. This research was conducted in the context of modern family relationships in the digital era. The respondents in this study were 4 informants, namely students aged 18 - 22 years who actively use the WhatsApp application in daily communication and 3 supporting informants (the students' parents). The findings of this research reveal communication patterns, usage habits, perceptions, and the impact of WhatsApp use on parent-child relationships. The results of this research provide valuable insight into how WhatsApp is used in the family context, as well as the implications of using the application for the dynamics of interactions between parents and children. It is hoped that this research can contribute to further understanding of the role of technology in modern family relationships and provide a basis for the development of interventions or programs that promote healthy and productive communication between parents and children in the digital era where accelerated communication can penetrate space and time with Using communication media in the form of the WhatsApp application has a positive impact on users, starting from text messages, voice messages, picture and video messages. This application answers the needs of parents when children are far from their parents, where from this research it is known that the WhatsApp application is one of the media that supports the development of communication technology which has a positive impact in the dromology theory which explains the acceleration of communication, but there is no visible anxiety or worry for WhatsApp application users